Safety and efficacy of intravesical instillation of botulinum toxin-A in the treatment of interstitial cystitis/bladder pain syndrome and overactive bladder: a systematic review and meta-analysis - Zhou, Yongheng; He, Zitian; Xiang, Tianyu; Cao, Xiaoyan; Cong, Huiling; Liu, Qinggang; Sun, Haoyu; Liao, Limin (Frontiers in Pharmacology, 2025)
BackgroundThe effectiveness and safety of the instillation of botulinum toxin A (BTX-A) remain subjects of controversy. The meta-analysis was performed to assess the efficacy and safety of a novel intravesical instillation of BTX-A for managing overactive bladder (OAB) or interstitial cystitis/bladder pain syndrome (IC/BPS).MethodThe randomized controlled trials were retrieved from PubMed, EMBASE, and the Cochrane Library databases up to 29 January 2024. The studies included in the analysis focused on the intravesical instillation of BTX-A in patients with OAB or IC/BPS. The data extraction was independently conducted by two reviewers. The random effects model was utilized for the assessment in order to compute the overall effect sizes. The heterogeneity tests and subgroup analyses were conducted.ResultsThe meta-analysis and subgroup analysis did not reveal any statistically significant differences. However, the results of the meta-analysis indicated that intravesical instillation of BTX-A could reduce episodes of urgency urinary incontinence (UUI) (overall weighted mean difference [WMD] = −0.85; 95% confidence interval [CI]: -2.99 to 1.29). In subgroup analysis, an increase in void volume (VV) at 4 weeks of follow-up (WMD = −31.99; 95% CI: -70.53 to 6.54) was observed compared to that at 12 weeks (WMD = −1.73; 95% CI: -16.98 to 13.53). In contrast to the groups receiving more than 200 units of BTX-A, patients in the group receiving 200 units or fewer of BTX-A (WMD = −16.89; 95% CI: -41.14 to 7.35) exhibited a significantly greater increase in VV.ConslusionThe intravesical instillation of BTX-A appears to be a viable administration route that may reduce UUI and VV to some extent. In terms of safety, intravesical instillation of BTX-A demonstrated a reduced risk of UTI and post-void residual compared to the placebo group.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024517877.